Analisis Sektor Pertanian, Kehutanan dan Perikanan sebagai Sektor Berkelanjutan di Provinsi Sumatera Utara - Vany Putra Immanuel Panjaitan; Markus Patiung; Endang Siswati (Jurnal Ilmiah Sosio Agribis, 2022)
This study aims to analyze various sectors ranging from forestry, agriculture and fisheries which play a fundamental or prospective contributor to their role in regional gross domestic product, analysis of the patterns and structures of the forestry, agriculture and fisheries sectors, analysis of whether the forestry, agriculture and fisheries sectors are included in the developed sector where growth occurs rapidly,  or slow and even falling into the lagging sector. As based on LQ research, the Forestry, agriculture and fisheries sectors have an LQ value = 1.97 which is gained knowledge that the sectors mentioned are included in the base sector in North Sumatra Province. The juxtaposition between LQ and DLQ obtained a value of LQ = 1.97 and related to DLQ = 1.52, which in the end LQ > 1 and DLQ > 1, when knowledge was obtained that the Forestry, Agriculture and Fisheries sector was included in the seeded sector. This means that the three sectors that have been mentioned are classified as base sectors. The results of the analysis of the klassen typology provide clues that the results of the rik > ri and yik >yi, where the forestry, agriculture and fisheries sectors are included in the criteria for sectors that have advanced to grow rapidly.Keywords: Agribusiness Sector, GRDP, LQ, DLQ, Klassen Typology